2010
DOI: 10.1177/0883073809359540
|View full text |Cite
|
Sign up to set email alerts
|

SPRED 1 Mutations in a Neurofibromatosis Clinic

Abstract: Legius syndrome, caused by SPRED1 mutations, has phenotypic overlap with neurofibromatosis type 1 (NF1) without tumorigenic manifestations. Patients fulfilling the NIH diagnostic criteria for NF1 were enrolled from the University of Utah NF Clinic and SPRED1 mutation analysis performed in order to identify the frequency of Legius syndrome within an NF1 clinic population. SPRED1 sequencing was performed on 151 individuals with the clinical diagnosis of NF1 and 2 individuals (1.3%) were found to have novel SPRED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…The majority of reported Spred1 mutations produce a premature stop codon, resulting in C-terminally truncated protein products (Brems et al 2007;Messiaen et al 2009;Pasmant et al 2009;Spurlock et al 2009;Muram-Zborovski et al 2010;Denayer et al 2011;Laycock-van Spyk et al 2011;Spencer et al 2011). As the SPR domain has previously been reported to target Spred1 to the plasma membrane via interactions with phospholipids and caveolin-1 (Lim et al 2002;Nonami et al 2005), we surmised that the truncated mutants were unable to function as a result of mislocalization.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of reported Spred1 mutations produce a premature stop codon, resulting in C-terminally truncated protein products (Brems et al 2007;Messiaen et al 2009;Pasmant et al 2009;Spurlock et al 2009;Muram-Zborovski et al 2010;Denayer et al 2011;Laycock-van Spyk et al 2011;Spencer et al 2011). As the SPR domain has previously been reported to target Spred1 to the plasma membrane via interactions with phospholipids and caveolin-1 (Lim et al 2002;Nonami et al 2005), we surmised that the truncated mutants were unable to function as a result of mislocalization.…”
Section: Resultsmentioning
confidence: 97%
“…Initial experiments revealed that Spred1 mutations were loss-of-function mutations, incapable of inhibiting the Ras/MAPK pathway (Brems et al 2007). SPRED1 mutations account for at least 2% of the pathogenic mutations associated with patients clinically diagnosed with NF1 (Brems et al 2007;Messiaen et al 2009;Pasmant et al 2009;Spurlock et al 2009;Muram-Zborovski et al 2010;Denayer et al 2011;Laycock-van Spyk et al 2011;Spencer et al 2011).…”
mentioning
confidence: 99%
“…The presence of cutaneous neurofibromas was documented upon time of examination. Given that some individuals with Legius syndrome fulfill the diagnostic criteria for NF1 based on pigmentary findings, children were screened for SPRED1 mutations as previously reported, 28 and individuals with SPRED1 mutations consistent with Legius syndrome were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Mutated genes responsible for the regulation of cell fate, genome integrity, and survival can lead to increased protein amplification and alter the tumor microenvironment, thus overactivating the pathway . These mutations can occur upstream in membrane receptor genes, such as epithelial growth factor receptor ( EGFR ), in signal transducers ( RAS ), regulatory partners ( Sprouty ), and downstream kinases that belong to the MAPK/ERK pathway itself ( BRAF ) (Fig. ) .…”
Section: Introductionmentioning
confidence: 99%